Pembelajaran Tematik Muatan SBdP Menggunakan Media Video Pembelajaran Tari Daerah Bengkulu - Saskia Azizah; Dwi Anggraini; Bambang Parmadie (JURIDIKDAS, 2023)
This study aims to describe the thematic learning process for cultural arts and crafts content using the traditional dance of Bengkulu learning video media at elementary school 19 Bengkulu City.The type of research in this research is qualitative with descriptive study method. The research subject is fourth grade teacher and students. The research instrument used guidelines for observation, interviews and documentation. Data collection techniques using observation, interviews and documentation. Data is analyzed through data collection, Data reduction,data display, conclusion drawing/verification.The results of this study indicate that the thematic learning process for cultural arts and crafts content using traditional dance of Bengkulu learning video media at elementary school 19 Bengkulu City what the teacher has done has been used to the fullest, even though the videos available in the school archives are still videos taken by amateurs by the teacher concerned. Videos traditional dance of Bengkulu  that are applied by teachers at elementary school 19 Bengkulu City are offering dance, andun dance and serunai. Learning videos used by teachers support each stage of learning, namely: introduction, core and closing. Learning videos in preliminary activities can help students in apperception activities and explain learning objectives. The learning video in the core activity explains each step of learning carried out on the Bengkulu regional dance material, and the learning video for regional dance in the closing activity serves as the basis for giving rewards to students who have succeeded in practicing the art of traditional dance.